Electoral culture in Iraq and the role of communication media Social in its cognitive restructuring - Rumayd , Sabah Mahdi; Kazem, Falah Khalaf (The International and Political Journal, 2025)
The important study was devoted to the culture of society and liberalism in the formation and maturation of the culture of good people, especially as it is today illuminated by the foundations of democratic transformation within the framework of theory and practice. The idea of ​​this study was justified in light of the dangerous master phenomenon in the levels of participation of the Iraqi voter, whether in the 2021 elections or in the field of The 2023 governorate elections chose the problem and imposed the hypothesis to reach the results, which appeared to fall below the level of the chosen culture and its social choice was complicated by the actors of social media, and was determined by the axes of the study supported by contemporary public evidence.